Peasant farming and growth of capitalism in Indian agriculture editied by Y.V. Krishna Rao...[et.al] - "Krishna Rao, Y.V.(ed.)" (Vijayawada, 1984)
The Andhra Pradesh Ryotu Sangham had organised a three-day seminar at Hyderabad, from 10th to 12th September 1982, on the theme of development of capitalism in agriculture and the importance of the price question for the peasants. Recognising the need for an interaction and exchange of notes on these subjects between the interested academics and activists the Sangham had invited to the seminar social scientists, economists, histotians, political scientists, and activists working on these themes and in the Kisan and Kheth Mazdoor movements. Representation at the seminar was wide in the geographic sense, with participants coming from different regions.
Keywords: Agriculture-Economic aspects